SYNTHESIS OF CATIONIC CELLULOSE AS POLYMERIC SURFACTANTS - Dewi Sondari; Agus Haryono (Prosiding SNST Fakultas Teknik, 2010)
Abstract The synthesis of cationic cellulose dissolved in water was conducted at 50o for 2 hours continued at temperature 76oC for 15 minutes in a glass reactor. The cationic cellulose  was synthesized through one-step substitution reaction The chemical composition of cationic cellulose was analyzed by FTIR (Fourier-Transformed Infra-Red). The successful conjugation onto cellulose chain confirmed by 1H NMR (Nuclear Magnetic Resonance). Water solubility of cationic cellulose product was measured using UV-Visible spectrophotometer at 600 nm. Keywords: Cationic cellulose, polymeric surfactants, water- soluble polymer, 1H NMR, FTIR